Caracterización morfológica del pasto saboya M1 (Panicum maximum), expuestos a diferentes niveles de irradiación con rayos gamma (60Co) en el cantón Babahoyo - Cadena Sánchez, Edison Rolando (2020)
This research was carried out in order to morphologically characterize the M1 (Panicum maximum) savoy grass, exposed to different levels of gamma ray irradiation (60Co). This research work was carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road. The geographical coordinates in UTM were X: 1 772,346; Y: 79.7102593. The area has a humid tropical climate, with a temperature that ranges between 24 and 26 ° C, with relative humidity of 88%, annual average rainfall of 1 262 mm, with a height of 8 meters above sea level and 990 hours of annual average heliophany. As evaluation material, Savoy grass plants were used, coming from the material irradiated at 0, 50, 75, 100 and 150 Gy of gamma rays (60 Co). To evaluate the variability of phenotypic characteristics of the Savoy grass, characterizers used for other studies of the same nature were adapted. As a result, it could be evidenced that the irradiation levels applied in the T3 treatment with a dose of 75 GY reported 2,48 m in height and was higher than the rest of the treatments. With respect to the stem diameter, the T2 treatments with a dose of 50 GY and T5 with a dose of 150 GY, with 5.6 and 6.1 respectively were statistically superior to the rest of the treatments. As for the variable leaf length, the T3 treatment with a dose of 75 GY, obtained a longer leaf length, with 161,6 cm. In the variable number of stems T3 with a dose of 75 GY and T4 with doses of 100 GY, they obtained the highest number of stems, with 5,8 and 5,6 respectively, were statistically superior to the rest of treatments. In the variable yield it can be observed that the highest value was given for the T4 treatment with a level of 100 GY with a wet weight of 275,30 grams, for the dry weight the best treatment corresponds to T3 with a level of 75 GY with a value of 112,40.